2012
DOI: 10.1016/j.ypmed.2012.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Automobile commuting duration and the quantity of time spent with spouse, children, and friends

Abstract: This was the first study to utilize time diary data to explore the relationship between commuting length and time spent with others. These estimates will inform researchers interested in time usages' impacts on physical and mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 16 publications
3
30
0
1
Order By: Relevance
“…In countries where the public transport system is not well developed, daily experiences of unreliable transport, conflicting time schedules, congested roads and crowded trains contribute to commuters' physical and psychological stress (Cantwell et al 2009). Increases in commuting time among male workers have been shown to be associated with significant decreases in time spent with their spouse, children, and friends (Christian 2012). Parents who had a long commute to work and whose child spent a long time unsupervised after school reported high levels of parental after-school concerns (Barnett and Gareis 2006).…”
Section: Fathers' Commute To Work and Child Well-being In Germanymentioning
confidence: 99%
See 2 more Smart Citations
“…In countries where the public transport system is not well developed, daily experiences of unreliable transport, conflicting time schedules, congested roads and crowded trains contribute to commuters' physical and psychological stress (Cantwell et al 2009). Increases in commuting time among male workers have been shown to be associated with significant decreases in time spent with their spouse, children, and friends (Christian 2012). Parents who had a long commute to work and whose child spent a long time unsupervised after school reported high levels of parental after-school concerns (Barnett and Gareis 2006).…”
Section: Fathers' Commute To Work and Child Well-being In Germanymentioning
confidence: 99%
“…Parental time for children is an important familial resource which enables parents to promote optimal child development (Brooks-Gunn et al 1995;Daly 1996;Huston and Bentley 2010;Neymotin 2014;Zubrick et al 2005), through developing close parent-relationships, helping young children to form secure FATHERS' COMMUTE TO WORK AND CHILD WELL-BEING IN GERMANY attachment and to develop cognitive skills (Bradley 2002) and emotional capacities, such as regulating emotions, dealing positively with frustration, and delaying gratification (Eisenberg and Valiente 2002). Long commutes to work diminish the quantity of this recourse (Christian 2012) as commuting increases the total number of hours which parents spend away from the home. Fathers who commute a long distance to work on a weekly basis reported that commuting limited their opportunity to participate in childrearing and reduced communication with their spouse (Hogarth 1987).…”
Section: Theoretical Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Due to its association with obesity in adults as well as potential associations with caregiver health behaviors, commute times in particular may be an important factor to consider when providing diet and lifestyle counseling. 8,9 Future research should include examining associations between family diet and activity and self-reported caregiver commute times.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 On a neighborhood level, areas with longer average CTW times and a higher dependency on vehicles tend to have a higher prevalence of obesity. 10,11 The association between commute time and obesity is thought to be mediated by the reallocation of time from physical activity and other potentially healthy behaviors to the sedentary, often stressful task of commuting.…”
Section: Introductionmentioning
confidence: 99%